Plant diversity drives soil carbon sequestration: evidence from 150 years of vegetation restoration in the temperate zone - Tian, Qilong; Zhang, Xiaoping; Yi, Haijie; Li, Yangyang; Xu, Xiaoming; He, Jie; He, Liang (Frontiers in Plant Science, 2023)
Large-scale afforestation is considered a natural way to address climate challenges (e.g., the greenhouse effect). However, there is a paucity of evidence linking plant diversity to soil carbon sequestration pathways during long-term natural restoration of temperate vegetation. In particular, the carbon sequestration mechanisms and functions of woody plants require further study. Therefore, we conducted a comparative study of plant diversity and soil carbon sequestration characteristics during 150 years of natural vegetation restoration in the temperate zone to provide a comprehensive assessment of the effects of long-term natural vegetation restoration processes on soil organic carbon stocks. The results suggested positive effects of woody plant diversity on carbon sequestration. In addition, fine root biomass and deadfall accumulation were significantly positively correlated with soil organic carbon stocks, and carbon was stored in large grain size aggregates (1–5 mm). Meanwhile, the diversity of Fabaceae and Rosaceae was observed to be important for soil organic carbon accumulation, and the carbon sequestration function of shrubs should not be neglected during vegetation restoration. Finally, we identified three plants that showed high potential for carbon sequestration: Lespedeza bicolor, Sophora davidii, and Cotoneaster multiflorus, which should be considered for inclusion in the construction of local artificial vegetation. Among them, L. bicolor is probably the best choice.